Evolution of lower respiratory tract surgery - Bakhromova Odina Alisherovna; Eshonkhodjaev O.D; Khayaliev R.Y; Tursunov N.T; Rikhsiev Z.G (Peerian Journals Publishing, 2024)
This article studies the evolution of lower airway surgery. Today, early innovative diagnosis and prevention of tracheal defects is one of the most urgent problems in medicine.
Keywords: Evolution; instrumental diagnostics; defects